Indirect measurement of acoustic power into a small room at low frequencies - Duarte, Elisabeth de A.C.; Moorhouse, Andy; Viveiros, Elvira B. (Applied acoustics, 2012)
[Display omitted] ► The ‘peak envelope method’ is the power radiated measurement into the receiver room. ► The method employs two microphones and a calibrated volume velocity source. ► No reverberation time measurements are required. ► Good agreements in numerical and experimental validations were found. ► The method is apt for modal frequencies measurement where ISO 140 is badly adapted. An essential step towards improving sound insulation is a reliable means of quantifying the performance. However, for various reasons sound insulation measurements at low frequencies are associated with relatively high uncertainty and wide variance values. The objective of this research is to develop a method of sound insulation measurement which complements the standard ISO 140 measurement methods by providing improved accuracy at low frequencies. In this paper part of the problem is considered, namely the measurement of power radiated into the receiver room. The ‘peak envelope method’ is based on mode theory and the measurement employs a pair of microphones in the receiver room and a calibrated volume velocity source. No reverberation time measurements are required. The theory is outlined and computer simulations and trial measurements are carried out in order to validate the theory. Good agreement in numerical and experimental validation is demonstrated. We conclude that the peak envelope method is suitable for the measurement of radiated sound power at modal frequencies where ISO 140 methods are poorly adapted. In order to obtain transmission loss, a measure of incident power in the source room will also be required, which will be the subject of future works.